Male fetal sex affects uteroplacental angiogenesis in growth restriction mouse model. Issue 4 (18th January 2021) - Hebert, Jessica F; Millar, Jess A; Raghavan, Rahul; Romney, Amie; Podrabsky, Jason E; Rennie, Monique Y; Felker, Allison M; O'Tierney-Ginn, Perrie; Morita, Mayu; DuPriest, Elizabeth A; Morgan, Terry K
Abstract: Abnormally increased angiotensin II activity related to maternal angiotensinogen (AGT) genetic variants, or aberrant receptor activation, is associated with small-for-gestational-age babies and abnormal uterine spiral artery remodeling in humans. Our group studies a murine AGT gene titration transgenic (TG; 3-copies of the AGT gene) model, which has a 20% increase in AGT expression mimicking a common human AGT genetic variant (A[−6]G) associated with intrauterine growth restriction (IUGR) and spiral artery pathology. We hypothesized that aberrant maternal AGT expression impacts pregnancy-induced uterine spiral artery angiogenesis in this mouse model leading to IUGR. We controlled for fetal sex and fetal genotype (e.g., only 2-copy wild-type [WT] progeny from WT and TG dams were included). Uteroplacental samples from WT and TG dams from early (days 6.5 and 8.5), mid (d12.5), and late (d16.5) gestation were studied to assess uterine natural killer (uNK) cell phenotypes, decidual metrial triangle angiogenic factors, placental growth and capillary density, placental transcriptomics, and placental nutrient transport. Spiral artery architecture was evaluated at day 16.5 by contrast-perfused three-dimensional microcomputed tomography (3D microCT). Our results suggest that uteroplacental angiogenesis is significantly reduced in TG dams at day 16.5. Males from TG dams are associated with significantly reduced uteroplacental angiogenesis from early to late gestation compared with their female littermates and WT controls. Angiogenesis was not different between fetal sexes from WT dams. We conclude that male fetal sex compounds the pathologic impact of maternal genotype in this mouse model of growth restriction. Abstract : Male fetal sex affects maternal uterine spiral artery angiogenesis and placental efficiency leading to intrauterine growth restriction.